The Effect of Low-Level Laser Therapy on the Acceleration of Orthodontic Tooth Movement - Baghizadeh Fini, Maryam; Olyaee, Pooya; Homayouni, Ahmadreza (Journal of Lasers in Medical Sciences, 2020)
In clinical practice, Low-Level Laser Therapy (LLLT) is widely used. The main aim of this review is to assess the effectiveness of LLLT on accelerating tooth movement in human subjects. The PRISMA checklist was utilized as a guideline to carry out this systematic review. The electronic databases were searched from Google Scholar (2014-2018) and PubMed, and comprehensive research on this topic was also manually conducted. Therefore, 76 Randomized Clinical Trials (RCT) or Controlled Clinical Trials (CCT) articles were selected. After screening studies, consequently, ten trials met the inclusion criteria. Eight out of ten studies showed LLLT has a significant impact on the acceleration of orthodontic tooth movement, and there was no statistically significant difference in the rate of tooth movement between the laser group and the control group in the two remaining studies. Furthermore, five out of ten articles showed that LLLT has no adverse effects. Although we have some degree of understanding from a cellular point of view to low-level laser therapy effects, we still do not know whether this cellular level changes have any effect on clinical acceleration of the orthodontic tooth movement. The results are inconclusive and cannot be generalized to the public community; therefore, well-structured studies are required.